A Review On Online Focus Group Discussion During The Covid-19 Pandemic - Amin Al Haadi Shafie; Dini Farhana Baharudin; Ahmad Najaa' Mokhtar; Mohd Khairul Anuar Rahimi; Khatijah Othman; Rafidah Aga Mohd Jaladin; Salleh Amat; Nurhafizah Mohamad Yasin; Suzaily Wahab; Nur Fatinni Mohamad Kama (ResearchTrentz, 2024)
Indexed by Scopus/ERA